The starburst galaxy NGC 253 revisited by H.E.S.S. and Fermi-LAT - Abdalla, Hassan; Glawion, Dorit; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Rieger, Frank M.; Schwemmer, Stephanie; Wagner, Stefan (Astronomy and astrophysics, 2018)
Context. NGC 253 is one of only two starburst galaxies found to emit γ-rays from hundreds of MeV to multi-TeV energies. Accurate measurements of the very-high-energy (VHE; E > 100 GeV) and high-energy (HE; E > 60 MeV) spectra are crucial to study the underlying particle accelerators, probe the dominant emission mechanism(s) and to study cosmic-ray interaction and transport.Aims. The measurement of the VHE γ-ray emission of NGC 253 published in 2012 by H.E.S.S. was limited by large systematic uncertainties. Here, the most up to date measurement of the γ-ray spectrum of NGC 253 is investigated in both HE and VHE γ-rays. Assuming a hadronic origin of the γ-ray emission, the measurement uncertainties are propagated into the interpretation of the accelerated particle population.Methods. The data of H.E.S.S. observations are reanalysed using an updated calibration and analysis chain. The improved Fermi-LAT analysis employs more than 8 yr of data processed using pass 8. The cosmic-ray particle population is evaluated from the combined HE-VHE γ-ray spectrum using NAIMA in the optically thin case.Results. The VHE γ-ray energy spectrum is best fit by a power-law distribution with a flux normalisation of (1.34 ± 0.14stat ± 0.27sys) × 10−13 cm−2 s−1 TeV1 at 1 TeV - about 40% above, but compatible with the value obtained in . The spectral index Γ = 2.39 ± 0.14stat ± 0.25sys is slightly softer than but consistent with the previous measurement within systematic errors. In the Fermi energy range an integral flux of F(E > 60 MeV) = (1.56 ± 0.28stat ± 0.15sys) × 10−8 cm−2 s−1 is obtained. At energies above ∼3 GeV the HE spectrum is consistent with a power-law ranging into the VHE part of the spectrum measured by H.E.S.S. with an overall spectral index Γ = 2.22 ± 0.06stat.Conclusions. Two scenarios for the starburst nucleus are tested, in which the gas in the starburst nucleus acts as either a thin or a thick target for hadronic cosmic rays accelerated by the individual sources in the nucleus. In these two models, the level to which NGC 253 acts as a calorimeter is estimated to a range of fcal = 0.1 to 1 while accounting for the measurement uncertainties. The presented spectrum is likely to remain the most accurate measurements until the Cherenkov Telescope Array (CTA) has collected a substantial set of data towards NGC 253.